Determining the Spoilage Threshold for Ground Beef Using Microbial, Color, and Oxidation Measures - Lauren M. Frink; Stephanie L. Witberler; Mason J. Prester; Erin S. Beyer; Michael D. Chao; Morgan D. Zumbaugh; Jessie L. Vipham; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this study was to determine the point at which ground beef becomes spoiled relative to microbiological, lipid oxidation, and color measurements. Study Description: One lb ground beef packages from a case-ready facility were stored at 36 to 40°F in the absence of light until displayed in coffin-style cases under fluorescent lighting. The packages were assigned to one of eight display periods (0, 2, 4, 6, 8, 10, 12, and 14 days). Samples were evaluated by consumers for visual appearance, touch, and odor liking, as well as evaluated for discoloration, redness, off-odor presence, and characteristic beef texture by trained sensory panelists. Additionally, objective measurements of aerobic plate counts (APC), Enterobacteriaceae plate counts (EB), and Escherichia coli (E. coli) coliform plate counts (ECC) for microbiology were obtained along with thiobarbituric acid reactive substances (TBARS) for lipid oxidation and L* (lightness), a* (redness), and b* (yellowness) values for color. Results: Logistic regression models were generated to identify purchase intent thresholds and consumer spoilage classification based on the objective measures. Consumer appearance liking showed the strongest predictor values relative to the microbiological assays, explaining 81% of the variation when predicting consumer purchase intent. Logistic models for APC (R2 = 0.59; P < 0.05) identified values of 7.3, 6.7, 6.1, and 5.8 log colony forming units (CFU)/g representing 50, 75, 90, and 95% likelihood a consumer would purchase the product. Additionally, APC values (R2 = 0.46; P < 0.05) of 5.3, 5.9, 6.8, and 7.7 log CFU/g relating to 5, 10, 25, and 50% likelihood a consumer would consider a product spoiled. The EB and ECC models also showed the strongest relationships corresponded to appearance liking, but were not as relevant as the APC predictors. Overall, all objective measurements in relation to consumer appearance liking explained the most (P < 0.05) variance within the model. The Bottom Line: Though changes in objective measures occurred throughout 14 days of display, the strongest determining factor when predicting consumer purchase intent and spoilage was the consumer appearance liking scores.
Keywords: ground beef; spoilage; consumer